Influence of aesthetic coating on the load-deflection ratio of nickel-titanium archwires - Marcus Vinicius Neiva Nunes do Rego; Gislayne Maria Mesquita de Araújo; Elizabeth Ferreira Martinez; Kássio Rafael de Sousa Lima; Pio Thiago Feitosa Fortes; Leanne Matias Portela Leal (Universidade Estadual de Campinas, 2017)
Aim: To assess the influence of aesthetic surface coating on load-deflection ratios in nickel-titanium (NiTi) orthodontic wires compared with uncoated wires.Methods: NiTi wires (0.016") from four different manufacturers (Morelli, Sorocaba, SP, Brazil; TP, La Porte, IN, USA; Eurodonto, Curitiba, PR, Brazil; Ortho Organizers, San Marcos, CA, USA) were divided into eight groups, according to presence or absence of coating: group 1, Morelli coated wire; group 2, Morelli uncoated; group 3, TP coated; group 4, TP uncoated; group 5, Eurodonto coated; group 6, Eurodonto uncoated; group 7, Ortho Organizers coated; group 8, Ortho Organizers uncoated. To determine the load-deflection ratio, a three-point bending test was performed in a AGS-X 250 KN (Shimadzu) universal testing machine.Results: The results showed that aesthetic coatings did not influence load-deflection ratio in NiTi orthodontic wires at 1-mm and 2-mm activation. However, comparison across the four tested brands revealed that Eurodonto coated wires exhibited the greatest force levels at 1-mm, 2-mm, and 3-mm deflection. At 3-mm deflection, Ortho Organizers coated wires exhibited lower force levels than all other tested brands, except for TP wires.Conclusions: We conclude that the load-deflection ratio of NiTi wires was not influenced significantly by aesthetic coatings, especially at lower activations.